Analisis Deskriptif Penerapan Kecerdasan Buatan, Prediksi Integritas, Kinerja Keuangan dan Ukuran Perusahaan di Perbankan Indonesia dan Singapura Tahun 2021 – 2023 - Regina Jansen Arsjah; Gresia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the application of artificial intelligence, integrity prediction, financial performance, and company size in the Indonesian and Singapore banking sectors during the 2021-2023 period. Secondary data is used in this study, including annual reports, financial reports, and other relevant data sources. The quantitative descriptive method was applied to analyze the collected data. The results show that the adoption of artificial intelligence in the banking sector has had a positive impact on operational efficiency, fraud detection, and risk management. In addition, corporate integrity prediction plays an important role in maintaining the stability and reputation of financial institutions, with artificial intelligence technology assisting in detecting potential risks and fraudulent activities. This study also found that firm size, as measured by total assets, contributes significantly to bank financial performance. These findings make an important contribution to the literature and provide insights for policy makers and banking practitioners to optimize the use of artificial intelligence technology and integrity prediction in improving firm performance and competitiveness.